Enhancing Grid Efficiency in Yavatmal: A Case Study on Advanced Efficient Storage System - Pratik Rameshwar Raut; Tanvi Ravindra Fatkar; Pranjali Dilip Fulkar; Sahil Sunil Latankar; Jitendra Sawant (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
As growing population in this world, the power consumption is increasing with respect the population, at this time more solar and wind power generation work together generate the power own field. at this time too much shorter of the energy consumption that is require to store some energy. Due to some mismatch of peal hour demand consumption of power, it is necessary to store the energy. The smart grid defined as the something of the ecosystem with communicate with the virtual self- ware system also it will require some advanced tool for planning and operations. In some year back mostly, smart grid used in renewable energy due to economical and environment friendly. Energy storage system with collaboration of smart grid gives a bright impact on our future. With the help of various communication and control feature it is possible to established the energy storage system as well as battery storage system. This paper gives all the detailed to store the energy in smart grid manner. The adoption of Smart Grid devices throughout utility networks will affect tremendous change in grid operations and usage of electricity over the next two decades. The changes in ways to control loads, coupled with increased penetration of renewable energy sources, offer a new set of challenges in balancing consumption and generation. Increased deployment of energy storage devices in the distribution grid will help make this process happen more effectively and improve system performance. This paper addresses the new types of storage being utilized for grid support and the ways they are integrated into the grid.
Keywords: Energy; Storage; System; Smart; Grid; Yavatmal; Grid Energy Management; Battery Energy Storage; Renewable Energy Integration